2009
DOI: 10.4314/jmbr.v5i2.10687
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Lower Respiratory Tract Infection in Benin City, Nigeria

Abstract: Patients with respiratory tract infections (RTI), Pneumonia inclusive account for a large proportion of a primary care physicians (PCP) work load and a frequent cause for prescription of antibacterial agents.The study was aimed at analyzing the various isolated organisms obtained from sputum and to test their susceptibility and sensitivity to available antibiotics in use in the hospital and environ. Two hundred and forty eight patients seen over a one year period (January 1, 2005 to December 31, 2005) and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
36
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 7 publications
22
36
7
Order By: Relevance
“…A similar study in Nigeria showed LRTIs was 54.80% in male and 67.10% in female [7]. Gender has varied impact on bacterial incidence as some studies show higher infection in females [21] while others show more in males [20]. Higher growth reported among men in our study might be due to lifestyle factors like smoking and alcohol consumption [7].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A similar study in Nigeria showed LRTIs was 54.80% in male and 67.10% in female [7]. Gender has varied impact on bacterial incidence as some studies show higher infection in females [21] while others show more in males [20]. Higher growth reported among men in our study might be due to lifestyle factors like smoking and alcohol consumption [7].…”
Section: Discussionsupporting
confidence: 53%
“…The frequent incidence of P. aeruginosa in the sputum may be owing to their ability to colonize a wide range of ecological niches, such as air polluting agents, animal hosts and humans [19]. S. pneumoniae was isolated in 6.67% sputum samples in our study, but in most of the other similar world-wide studies, S. pneumoniae has been reported as the chief isolate [7,20,21]. In the present study, the prevalence of K. pneumoniae was 8.67% in the sputum samples.…”
Section: Discussionmentioning
confidence: 42%
“…The male predominance could be attributed to increasing incidence of smoking and alcohol consumption among males as reported in other studies [21, 22], or probably because females have less access to health care in our country.…”
Section: Discussionsupporting
confidence: 49%
“…Current knowledge of the organisms that cause LRTIs and their antibiotic susceptibility profiles are therefore necessary for the prescription of appropriate therapy [9]. Changes in the characteristics of the population as it ages and the swelling numbers of patients with immunocompromising conditions have increased the number of individuals at risk [2].…”
Section: Introductionmentioning
confidence: 99%